THE EFFECT OF TRUST AND SERVICE ON CUSTOMER LOYALTY AMELIA BAKERY AND CAKE BENGKULU CITY - Sari, Dwi Afila; Puspita, Veny; Waliamin, Janusi (Jurnal Signaling, 2024)
Customer loyalty is one of the things that determines the success of a business. Customer loyalty is formed by many determining factors, including trust and service. The purpose of this study was to determine how much influence trust and service have on customer loyalty both partially and simultaneously.The research method used is explanatory research, with the research population being Amelia Bakery and Cake customers. The number of samples was 130 respondents with purposive sampling data collection method with the criteria that Amelia Bakery and Cake customers are at least 16 years old and shop at least 3 times. The data was analyzed using SPSS with multiple linear regression analysis methods. The research results are: 1) trust variables partially have a significant effect on customer loyalty at Amelia Bakery and Cake, 2) service variables partially have a significant effect on customer loyalty at Amelia Bakery and Cake and 3) trust and service simultaneously have a significant effect on customer loyalty at Amelia Bakery and Cake.